Clostridioides difficile Infections in Children: What Is the Optimal Laboratory Diagnostic Method? - Mohammed Suleiman; Patrick Tang; Omar Imam; Princess Morales; Diyna Altrmanini; Jill C. Roberts; Andrés Pérez-López (Microorganisms)
The diagnosis of Clostridioides difficile infection (CDI) in the pediatric population is complicated by the high prevalence of asymptomatic colonization, particularly in infants. Many laboratory diagnostic methods are available, but there continues to be controversy over the optimal laboratory testing approach to diagnose CDI in children. We evaluated commonly used C. difficile diagnostic commercial tests in our pediatric hospital population at Sidra Medicine in Doha, Qatar. Between June and December 2023, 374 consecutive stool samples from pediatric patients aged 0–18 years old were tested using: Techlab C. diff Quik Chek Complete, Cepheid GeneXpert C. difficile, QIAstat-Dx Gastrointestinal Panel, and culture using CHROMagar C. difficile. The results of these tests as standalone methods or in four different testing algorithms were compared to a composite reference method on the basis of turnaround time, ease of use, cost, and performance characteristics including specificity, sensitivity, negative predictive value, and positive predictive value. Our study showed variability in test performance of the different available assays in diagnosing CDI. In our population, a testing algorithm starting with Cepheid GeneXpert C. difficile PCR assay or QIAstat-Dx Gastrointestinal panel as a screening test followed by toxin immunoassay for positive samples using the Techlab C. diff Quik Chek Complete kit showed the best performance (100% specificity and 100% positive predictive value) when combined with clinical review of the patient to assess risk factors for CDI, clinical presentation, and alternative causes of diarrhea.